Key insights to understand the immunogenicity of FVIII products - Goudemand, Jenny; Peyvandi, Flora; Lacroix-Desmazes, Sébastien (Thrombosis and Haemostasis, 2016)
The treatment of haemophilia has made significant progress in recent decades, and patients are now being treated safely with great clotting products. However, inhibitor development remains the largest problem, particularly in children. Consequently, the haemostasis that was obtained with traditional clotting factors is not being achieved. Moreover, inhibitor complications translate into adult life and there are an increasing number of situations where adult patients with an inhibitor require major surgery but the clinician is faced with the knowledge that required haemostasis levels are difficult to achieve. Therefore, it is of upmost importance to consider factors relating to inhibitor development, and to determine how inhibitors can be prevented and/or eliminated. Of the various factors at play with regard to inhibitor development, it is important to consider the immunogenicity of factor VIII (FVIII) products, and this topic is the focus of the current paper.
Keywords: Haemophilia; FVIII concentrates; immunogenicity; inhibitor; von Willebrand factor